Focal mechanism of the 5.1Mw 2014 Lloja earthquake, Bolivia: Probing the transition between extensional stresses of the central Altiplano and compressional stresses of the sub-Andes. (April 2019) - Fernandez, Gonzalo A.; Assumpção, M.; Nieto, M.; Griffiths, T.; Convers, J.
Abstract: The 2014 Lloja earthquake with 5.1 Mw occurred in the Eastern Cordillera of Bolivia between the Subandean belt (characterized by reverse and thrust faulting) and the Altiplano (where extensional stresses due to gravitational collapse dominate). Determination of the Lloja focal mechanism, therefore, is important to sample the transition between these two Andean stress provinces. In addition, two different moment tensor inversions had been published: a strike-slip solution with a normal component (NEIC-USGS) and a purely strike-slip solution (GCMT). A detailed relocation of the epicenter was carried out using two data sets: a) only the local stations of the La Paz network with a 1D model appropriate for the Central Andean plateau, and b) local + regional stations with the 3D RSTT model. Both epicenters agree within their uncertainties of about +- 5 km each. P-wave polarity of the local and regional stations, together with the S-wave polarity at LPAZ station, allowed the focal mechanism to be determined as a strike-slip solution with a small normal component, similar to the USGS solution. One nodal plane strikes NNE-SSW and was interpreted as the seismogenic fault because of its consistency with a) the distribution of the relocated aftershocks, and b) the NE-SW trending local Caracato - Rio La Paz geological fault near the epicenter. The strike-slip mechanism with a small component of normal faulting is consistent with a gradual transition between compressional stresses in the sub-Andean belt and extensional stresses in the Altiplano. Highlights: This Eastern Cordillera strike-slip earthquake probes the transition between Subandean compressional and Altiplano extensional stresses. The focal mechanism with first motions from regional stations and synthetics for LPAZ favors the USGS solution rather than the GCMT. 3D epicentral location and relative location of aftershocks helped identify the NE-SW striking Carato – Rio La Paz as the seismogenic fault.